2015
DOI: 10.1103/physrevb.92.165303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a noisy driving field on a bistable polariton system

Abstract: International audienceWe report on the effect of noise on the characteristics of the bistable polariton emission system. The present experiment provides a time-resolved access to the polariton emission intensity. We evidence the noise-induced transitions between the two stable states of the bistable polaritons. It is shown that the external noise specifications, intensity and correlation time, can efficiently modify the polariton Kramers time and residence time. We find that there is a threshold noise strength… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…The principle of the experiment is depicted in Fig. 5: the excitation laser (red dot on the right figure) is slightly detuned from the ground state (here in a 3-μm-diameter mesa) [50].…”
Section: Bistabilitymentioning
confidence: 99%
“…The principle of the experiment is depicted in Fig. 5: the excitation laser (red dot on the right figure) is slightly detuned from the ground state (here in a 3-μm-diameter mesa) [50].…”
Section: Bistabilitymentioning
confidence: 99%
“…2 is caused by the sensitivity of the experiment to intrinsic noise, especially close to the thresholds. Since we need a longer integration time to acquire the spectra compared to the spatially integrated measurements with the power meter (instantaneous value), we increase the probability of the system to undergo a noise-induced jump [32].…”
Section: Spatial Multistabilitymentioning
confidence: 99%
“…The bistability and spinor multistability of a microcavity polariton have been extensively studied both theoretically [16][17][18][19][20][21][22] and experimentally [23][24][25][26][27][28][29][30][31][32]. It relies on exciting the microcavity using a laser blue detuned with respect to the lower polariton branch (LP) and to measure the transmitted laser intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, previous works have shown that zerodimensional (0D) confined polaritons are ideal systems to investigate the polariton bistability [33][34][35][36] and particularly * clauderic.ouellet-plamondon@epfl.ch its sensitivity to noise [36][37][38]. The former study showed that a symmetrical collapse of the polariton hysteresis loop occurs for increasing noise strength on the polariton population.…”
Section: Introductionmentioning
confidence: 95%